Efforts to enhance first timer voter participation in regional elections through the socialization of democracy and regional autonomy at MAN 02 Samarinda - Devy Indah Paramitha; Dian Putriana; Alifah Roihanah Difa; Muhammad Kamarul Zaman; Ridho Syahbana; Astrid Herawati; Ghina Rifqi Muhammad; Desy Muchtar; Dewi Safitri; Muhammad Fadel Amal; Fiona Ridha Ramadhina; Maria Marleni; Iqbal Renaldy (Community Empowerment, 2024)
Head of regional elections are one of the mechanisms for creating a democratic system of government, especially at the regional level. Therefore, public participation is needed to support the implementation of regional elections so that it can produce the best leaders. Based on a CSIS survey, the 2024 general election was dominated by first-time voters aged 17-23 years. This community service activity was carried out as an effort to increase the participation of first-time voters in regional head elections in Samarinda City. The activity targeted 12th-grade students of MAN 2 Samarinda. Using the expository method, the material was delivered in verbal form and assessments were used to measure knowledge. The results of the community service showed an increase in students' understanding of democracy and regional autonomy by 87% at the post-test. This percentage is higher than the value at the pre-test, which was only 61%.